The Potential and Development Strategy of Samber Park Metro Lampung Tourism Object - Apriyani (ProBisnis : Jurnal Manajemen, 2022)
This study aims to describe the form of interpretation that is implemented in Samber Park Metro City Park and to analyze efforts to implement City Parks as educational tourism objects through the concept of interpretation. This study applies a qualitative methodology to Metro City Parks in the period October~December 2022. The results show that Metro City Park managers have implemented personal and non-personal interpretations in supporting the function of City Parks as public and cultural facilities as well as educational tourism objects. As well as the government's efforts to build a stage in the Samber Park area so that it can be used as a means of increasing education about art in Metro City. However, Park staff considers several aspects necessary for interpretation practice. For example, visitors who explore around the park without being guided by park staff can reduce the quality of the tourist experience. Park staff should also evaluate issues such as facilities not having information labels and labels that are too short and unclear and not using international languages. This study proposes five models for the development of interpretation, namely digital-based information management models (websites and social media); models of strengthening cooperation and partnerships; model of identification and evaluation of nonpersonal interpretation; personal and nonpersonal interpretation integration model; and collaboration and partnership models. This research increases the urgency of interpretation in supporting education-based tourism. This park offers an experience for visitors to see the historical atrium of the metro city and carry out educational and experiential learning activities while traveling.